First European quality of life survey social dimensions of housing - Domanski, Henryk; Ostrowska, Antonina; Przybysz, Dariusz; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
A good standard of housing is, along with level of income, an essential component of quality of life and a valid indicator of the material conditions of a household. In fact, having one's own personal space - an intimate sphere in which someone can regenerate and escape from the bustle of everyday life - is one of the most fundamental biological, psychological and social needs. It is necessary for family well-being, and crucial for raising children and for their socialisation. Ultimately, it is a place for rest and relaxation in which people spend a significant part of their everyday lives.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Electronic books